MENINGKATKAN KEMAMPUAN PEMAHAMNAN MATEMATIS SISWA MELALUI PEMBELAJARAN MATEMATIKA BERBANTUAN GEOGEBRA - Nasution, Eline Yanti Putri (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2015)
The purpose of this study  is to investigate and to describe the gain of students’ mathematical understanding ability through mathematics teaching and learning by using dynamic geometry software, Geogebra. This study uses a not equivalent control group design, that is control group and experiment group. Direct instruction is implemented in control group otherwise mathematics teaching and learning with using Geogebra is implemented in experiment group. The population of this study are allof junior high school students, the subject are two groups of seventh grade students and the object is studentss’ mathematical understanding ability. The sample is choosed with using purposive sample technique. This study use mathematical understanding ability test that analysed quantitatively into post-test and normalized gain of students’ mathematical understanding ability between the two groups. The analyse of the data result will answer the hypothesis, students’ understandingability who has studied and learntwith using Geogebra is better than students in direct instruction class.